Analisis Pengaruh Kualitas Pelayanan dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan (Studi Pada Rumah Teh "Ndoro Donker") - Endratama, Dewanto; , Dra. Wuryaningsih Dwi Lestari, M.M (2015)
This purpose of this research to 1) To analyze the impact of service quality on customer loyalty study on "Rumah Teh Ndoro Donker". 2) To analyze the effect of customer satisfaction on customer loyalty study on "Rumah Teh Ndoro Donker". The sampling method used in this study is simple random sampling where the researcher has a personal choice in selecting individuals who will be mambers of the sample. Respondents in this study is that consumers who come to the Rumah Teh Ndoro Donker. Methods of data analysis using multiple linear regression, whereas the hypothesis test using the F test, t test, and the coefficient of determination (R2). Based on the results of the analysis conducted this study indicate that the quality of service and customer satisfaction has a significant influence on customer loyalty.